Studies on the in vitro anticancer activity of Tabernaemontana Divaricata extract against colon cancer cell line - S. SUBHASHINI; M. PANDIMA DEVI (International Journal of Pharma and Bio Sciences, 2017)
Cancer is considered to be one of the leading causes of morbidity and mortality worldwide. For the past years, plants were known to possess metastatic tumor activities against numerous neoplastic cell lines. Also, nature merchandise represents a reservoir of various templates and it is being tapped to source novel metastatic tumour agents. Tabernaemontana divaricata has been employed in Ayurvedic formulations in recent days. Leaves and flowers of T. divaricata are employed in folk medicines by the Ayurvedic practitioners. It is a native of India and also different tropical regions. It may be a common plant that has been used historically for the treatment of various diseases. Also, the plant has been reported to be helpful for the treatment of cuts, inflammation, eye and skin diseases, wounds, diarrhea, ulcer and cancers. The aim of this study is to investigate the in vitro metastatic antitumour activity of methanolic extract on T.divaricata against HT-29 human carcinoma cell line. The methanolic extracts of the leaves and flowers of T.divaricata were examined for its effect on HT-29 cell line. It was administered by exploitation of Tryphan blue exclusion technique. The toxicity of T.divaricata against HT-29 cell was evaluated by MTT assay. The cell morphology of drug treated HT-29 cell line was studied by nuclear staining technique. From the performed assays, methanolic extract of those drugs show more anticancer activity on colon cell line (HT-29).